Pattern of Patients visited at the Non-Communicable Disease Control (NCDC) corner at an Upazilla Health Complex in Chattogram, Bangladesh - Chowdhury, Suman; Khaled, Md Ishtiaque (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background:Non-communicable diseases (NCDs) have emerged as a significant global health challenge, and a pressing public health concern in Bangladesh. The Non-Communicable Disease Control (NCDC) corners have been established in different upazilla health complexes throughout the country. Lohagara, being the southernmost upazilla of Chattogram district, plays a crucial role in addressing the growing burden of NCDs in the region. A comprehensive analysis of the patient population accessing healthcare services at the NCDC corner is essential to optimize the delivery of care and improve patient outcomes. Methods: This descriptive cross-sectional study was conducted on the patients’ records from the NCDC corner over 12 months. The patients were also interviewed. Data regarding demographic information, diagnoses, comorbidities were analysed. Result: This study delves into the patterns of patients seeking healthcare services at the NCDC corner. Among the 3,316 patients, diabetes mellitus (DM) was predominant (68.9%), hypertension (15.4%) and ischemic heart disease (2.0%) were also notable. Combinations of these conditions highlighted the importance of integrated care models, where the incidence of DM with HTN was 8.6%. The study revealed diverse occupational backgrounds, with retired male individuals forming a significant portion (46.34%), raising concerns about financial constraints. Notably, the group of 41-50 years showed the highest prevalence, followed by the age group of 31-40 years, indicating the urgency of interventions in early adulthood. Additionally, housekeepers constituted a large proportion (90.53%) of female patients, highlighting the need for targeted health education programs. Conclusion: It is crucial for healthcare professionals to understand the patterns of patients presenting at the NCDC corner to improve the management and care of individuals with chronic illnesses. Findings in this research would provide valuable insights for shaping effective healthcare policies and interventions, optimizing resource allocation, and enhancing patient adherence to treatment protocols at the Upazilla Health Complex, Lohagara, Chattogram, Bangladesh. J Bangladesh Coll Phys Surg 2025; 43: 116-121